Mediation in the draft Code of Civil Procedure: on problematic issues - Skobelev, Vladimir P. (Journal of the Belarusian State University. Law, 2022)
The author analyses how the draft Code of Civil Procedure regulates issues related to the use of mediation. It is shown that it is necessary to clarify (in the direction of narrowing) the range of disputes that can be resolved through mediation, specify the moment in the development of the process at which the parties are allowed to apply for mediation, exclude the possibility of leaving the statement of claim without consideration due to the conclusion by the parties of an agreement on the use of mediation, more clearly and consistently regulate the functions of the court regarding mediation (the court is not authorised to submit a dispute to mediation, but is obliged to sanction agreements on its application), settle all other (apart from the suspension of the proceedings or leaving the statement of claim without consideration) procedural consequences of the parties’ recourse to mediation.
Keywords: civil litigation; economic litigation; mediation; agreement on the use of mediation; mediation agreement; court; parties of the dispute; consequences of resorting to mediation